Perancangan Aplikasi Sistem Penilaian Kinerja Karyawan dengan metode MBO dan BARS (Studi Kasus PLTA Maninjau) - Taufik Nalda; Prima Fithri; Yudji Erman Prathama (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
Along with the development of science and technology today is so rapid, required human resource capacity and reliable quality which will support companies in improving the quality of the company. In response to the demanding needs of qualified human resources, Maninjau hydropower which is a branch of PT PLN and under Power Sector Bukittinggi, have tried to prepare the workforce to meet the requirements demanded by the busin ess. Way to do is to assess employee performance. Employee performance appraisal that applied hydropower Maninjau currently not able to see the performance and achievement of each employee. Hydroelectric Maninjau should improve the assessment of employees. The method can be done in assessing employee performance include the Management By Objectives (MBO) and Behaviorally Anchored Rating Scale (BARS). For the fast growing data needs, then designed an application performance appraisal in hydropower Maninjau with BARS and MBO method.Application design is done by surveying systems, system analysis, system design and performance of the MBO method BARS, employee performance appraisal application design, and manufacturing applications, as well as verification and validation. Making an application is done using Microsoft Excel. Once the application is successfully validated, then the application implementation. Implementation is based on the employee's performance on the most recent period, namely 1 last semester (January-June) were conducted in June, 2013.Based on the validation has been done, it can be concluded that the application has to be used by hydropower Maninjau in assessing employee performance. As for the results of the implementation of applications, it can be seen that the performance of the employee on hydropower Maninjau in the last period was on average 80%. The assessment includes an assessment of the achievement of business results and work with behavioral weight ratio, 60% for work objectives (MBO) and 40% for work behavior (BARS).